Diminutive freshwater fish in the Santa Cruz river system, Laguna, Philippines - Cui, Loucel E.; Guerrero, Rafael D., III; De Lara, Ayolani V.; Rebancos, Carmelita M.; Faustino-Eslava, Decibel V. (2022)
Diminutive freshwater fishes are small vertebrate species, maturing at sizes equal or less than 50-100 mm. The distribution and diversity status of these fishes are poorly known because they are difficult to observe in the wild due to their small size and remote location, especially in selected crater lakes, mountain streams, and waterfalls. The study provides baseline data for the diminutive freshwater fishes in the Santa Cruz River System in Laguna, Philippines. The survey was conducted in the upstream, midstream, and downstream for three quarters in 2016-2017. A total of 1,474 individuals belonging to nine families, 12 genera and 15 species were collected. Of the nine families, Gobiidae was the most abundant (47%) followed by Poeciliidae (18%) and Eleotridae (11%). Shannon-Weiner diversity indices ranged from 0.59 to 1.73. Dominance and Evenness ranged from 0.20-0.75 and 0.23 to 0.99 respectively. The study recommends preventive approaches over restorative actions for the conservation and protection of the diminutive fishery resource.
Keywords: Freshwater ecology